Factors affecting endoglucanase production by Trichoderma reesei RUT C-30 from solid state fermentation of oil palm empty fruit bunches using Plackett-Burman design - Abdul Wahid, Manisya Zauri; Salleh, Madihah; Yusof, Faridah; Abdul Karim, Mohamed Ismail; Alam, Md Zahangir (Academic Journals, 2011)
A study was conducted to screen parameters affecting the production of endoglucanase by Trichoderma reesei RUT C-30 on solid state fermentation of oil palm empty fruit bunch using the Plackett-Burman design. Factors involved in the screening process were peptone concentration, urea concentration, ammonium sulfate concentration, calcium nitrate concentration, yeast extract concentration, tween 80 concentration, pH, incubation time, initial moisture content, inoculum size and substrate amount. Through analysis of variance (ANOVA), it was found that initial moisture content (p=0.001), incubation time (p= 0.001), inoculum size (p= 0.032) and ammonium sulfate concentration (p=0.023) have been recognized as significant factors affecting endoglucanase activity in solid state fermentation (SSF) of oil palm empty fruit bunch (OPEFB) by T. reesei RUT C-30. The model established from the ANOVA analysis have a significant value of Pmodel>F= 0.0008 and R2 of 0.9132. The preoptimized media showed 2.6 fold increased of endoglucanase activity.